Root cause analysis of failure of bolts in the low pressure section of a gas turbine in an oil and gas production plant. (September 2020) - Mousavinia, M.; Bahrami, A.; Rafiaei, S.M.; Rajabinezhad, M.; Taghian, M.; Seyedi, S.J.
Highlights: Failure analysis of bolts in a gas turbine is investigated. Microstructural evolution during service exposure of bolts is investigated. The correlations between the microstructure and observed failure are discussed. The failure is related to the corrosion fatigue in rotating blades. Abstract: This research establishes the cause of a severe failure in bolts in the low pressure (LP) section of a gas turbine in an oil and gas production plant. The failure in bolts was reported together with massive failures of turbine blades in the second stage in the hot section of the turbine. The failure was categorized as an unexpected premature failure, given that it was reported to take place after 20 k of service and that the expected service life for this turbine is beyond 100 k. This research had a two-fold purpose; i) to analyse the cause of failure in both components (failed bolts and blades) and ii) to come up with a scenario for the chain of events. Standard microscopic examination techniques (optical metallography and electron microscopy) were used to correlate microstructure of failed components with possible failure mechanisms. Results showed a clear corrosion-fatigue-induced failure in blades. Hardly is there any evidence of fatigue failure in bolts. Bolts appeared to have experienced an excessive load and have consequently been heavily deformed and broken. The failure scenario was proposed, based on the service history, observations, and microstructural examinations.